The evaluation of digital educational game use in pharmacology teaching process - Marcin Mateusz Granat; Aleksandra Paź; Dagmara Mirowska‐Guzel (Wiley, 2024)
Abstract The aim of the study was to determine the usefulness of educational video games as a variety applied to the traditional teaching of pharmacology in topics of antifungal and hypolipidemic drugs. Sixty‐six volunteers were divided into control group (n = 33) and experimental group (n = 33). The first group received traditional seminar only, and the second played video game designed with the use of Kahoot! platform after the seminar. The assessment of knowledge was conducted with the use of three tests: pre‐test was presented before seminar, post‐test after seminar (for control group) or after playing the video game (for experimental group), and test no. 3 took place 4 weeks later. Analysis of tests' scores with respect to both topics resulted in the observation that the control and experimental groups show statistically significant improvement in knowledge, whether it was measured after the seminar or 4 weeks later. However, the results of experimental group were statistically better in comparison to the control group. It proves that electronic GBL (game‐based learning) applied to standard educational processes increases short‐ and long‐term knowledge retention compared to traditional seminars.